Phylogenetic Analysis of HPV16 Isolated from Women with Cervical Cancer Based on L2 Gene Partial Sequence in the Province of Dhi-Qar, Iraq - Jalil, Abduladheem Turki; Karevskiy, Aleksandr (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: As a causative agent for cervical cancer, the human papillomavirus (HPV) is well-recognized. Being a high-risk form, HPV16 is considered and has been confirmed to be associated specifically with cancer of the cervix. AIM: HPV16’s phylogenetic tree and genetic diversity are well known worldwide, but in Iraq, documents on HPV16 genetic diversity among women with cervical cancer are lacking; therefore, the present study focused on phylogenetic analysis of HPV16 isolated cervical cancer based on L2 gene partial sequence. METHODOLOGY: The current study focused on the investigation of HPV16 in women who suffer from cervical cancer. This survey was performed on 93 adult females suffering from cervical cancer during the period from 2017 to 2020. For the molecular study, DNA was extracted and subjected to a polymerase chain reaction (PCR) for detection and amplification of minor capsidprotein L2 gene. Nucleotide sequences of amplified capsid L2 gene were searched using the advanced simple local alignment search tool at GenBank (BLAST). RESULTS: Genetic screening on HPV16 L2 gene by conventional PCR showed that 60 (65%) of cervical cancer cases infected by HPV16 while only 5 (8%) of the healthy control group are positive for HPV16. The results of the NCBI-BLAST homology sequence showed that genetic variation appeared in four strains from five strains of HPV16. CONCLUSION: HPV16 from the main causative factors for cervical cancer with high genetic variation.